Study of malaria in febrile patients attending tertiary health care center and evaluation of peripheral smear examination, quantitative buffy coat and rapid diagnostic test in the diagnosis of malaria - Vidyasagar, K.; D., Venkatesha (International Journal of Research in Medical Sciences, 2022)
Background: The objective was to study the prevalence of malaria in febrile patients attending the hospital and to evaluate peripheral smear examination, quantitative buffy coat and rapid diagnostic test in the diagnosis of malaria. Methods: The study group includes 208 patients presenting with fever with chills and rigor and other suggestive symptoms of malaria attending the tertiary care center. 5 ml of venous blood was collected in ethylene diamine tetra acetate (EDTA) tube from each patient and the samples were processed for peripheral blood smear examination, quantitative buffy coat (QBC) and antigen detection by rapid diagnostic test (RDT). Results: Out of 208 suspected cases of malaria, 3 (1.44%) were positive for malaria and 205 (98.55%) were negative, the prevalence of malaria was found to be 1.44%. Of total 208 cases tested, 3 cases (1.44%) were positive for malaria by peripheral blood smear examination and by QBC and with rapid diagnostic test only 2 cases (0.96%) were positive. P. vivax was detected in all 3 positive cases. Conclusions: Peripheral smear examination is considered as gold standard method for diagnosis of malaria. QBC can be helpful when an experienced microscopist is not available. Rapid diagnostic tests are simple, rapid, do not need expertise, interpretation of results is easy and objective and useful in routine diagnosis.